Impact of carbon dioxide removal technologies on deep decarbonization of the electric power sector - John E. T. Bistline (Nature Portfolio, 2021)
Carbon dioxide removal technologies such as bioenergy with carbon capture and direct air can influence power sector planning and operations. Here the authors show how carbon removal options lower costs of deep decarbonization and alter electric sector investments.